Implementation of Vendor Managed Inventory (VMI) in Managing Inventory of Intra Ocular Lenses (IOL) in an Eye Care Organization - Sharma, Nancy; Singhi, Rushina (Prabandhan: Indian Journal of Management, 2016)
The Indian healthcare industry is a fast growing industry and needs attention for reengineering of many processes. The supply chain process is one of the important processes. But it lacks the attention of stakeholders due to which lack of efficiency of the process leads to direct or indirect impact on the businesses. Vendor managed inventory (VMI) is such a programe or tool that is still less used in the healthcare industry. VMI can help in increasing the efficiency of the supply chain process by delegating the responsibility of inventory management to the suppliers. The purpose of this paper was to measure the effectiveness of VMI over traditional inventory management system of IOLs (lenses that are used in surgeries of eye hospitals). A matrix was also designed to understand the key performance indicators of supply chain to assess the results of implementation of VMI in place of traditional managed inventory. True experimental design of quantitative research with pretest posttest was used to measure before and after impact of VMI on management of inventory of IOLs. A sample size of 14 types of lenses was taken to assess the impact of the VMI technique. Literature review of the traditional inventory management system and VMI was done and data was obtained from an eye care organization of inventory of IOLs to test the hypothesis to measure the effectiveness of VMI over traditional method of inventory management. The results concluded the success of VMI over traditional inventory management based on the performance indicators (OFR/TAT) of the supply chain.